MO264COMPLEMENT PATHWAY MIGHT HAVE A ROLE IN FOCAL SEGMENTAL GLOMERULOSCLEROSIS: A RETROSPECTIVE SINGLE CENTER STUDY OF 15 YEARS. (29th May 2021) - Eren Sadioğlu, Rezzan; Kiremitçi, Saba; Aktar, Merve; Şengül, Şule; Gokmen, Derya; Akturk, Serkan; Keven, Kenan; Nergizoglu, Gökhan; Ertürk, Şehsuvar; Ateş, Kenan; Ensari, Arzu; Kutlay, Sim
Abstract: Background and Aims: The role of complement in focal segmental glomerulosclerosis (FSGS) is an area of interest and C4d staining could indicate complement related renal damage. We investigated detailed C4d staining properties in native kidney biopsies and possible relation to clinical features. Method: We retrospectively evaluated the renal biopsies of 114 patients diagnosed with FSGS within last 15 years. C4d expressions examined in glomeruli (mesangial and/or capillary wall, vascular pole, sclerotic areas), tubular region (basement membrane, adsorbtion droplet) and vascular areas (arteriols and arteries) via immunohistochemistry. A novel glomerular C4d score (G-C4d-S) was achieved on the basis of the localization, pattern, extent and intensity of the C4d expression (min-max, 0-13). Results: Of the patients (56 females, mean age 43±14 years) with a median follow-up time of 35±3 months, mean proteinuria, eGFR, and albumin level were 4984 mg/day, 72.2 ml/min/1.73m 2, 3.56 g/dL, respectively. Median G-C4d-S was 6 (IQR, 4-7) and it was negatively correlated with serum creatinine at diagnosis (r=-0.21, p=0.02). Glomerular staining (both focal and diffuse, higher than moderate in intensity) was positive in 78 (68.4%) of the patients. C4d on glomerular sclerotic area was positive in 43 (37%) patients and it was associated with lower eGFR at diagnosis. Forty five patients achieved remission during the follow-up. Among the pathological features only glomerular C4d staining was associated to remission (p=0.02). There were 20 (18.7%) patients who need renal replacement theraphy (RRT) and 7 deaths (6.1%) at the end of the cohort. Lower rate of C4d staining on tubular adsorption droplets and arteriols/arteries were found to be associated need for RRT (p=0.013, p=0.012, respectively). There were no significant relationship between mortality and C4d staining features. Conclusion: In conclusion, we noted that significant number of patients had positivie C4d on glomeruli, arteiroles and tubular area. We indicated that C4d staining at diagnosis could help to distinguish active glomerulonephritis. Additionally, it seems to be essential to examine non-glomerular area of native kidney biopsies, as well.